Evaluating the efficacy of different doses of tocilizumab in treating critically ill COVID–19 patients: a single–center retrospective cohort study - Gao, Jie; Zhang, Wenjing; Ding, Yaru; Peng, Xinru; Wang, Jing; Li, Yuting; Gao, Jing; Cheng, Jie; Zhou, Wei; Zhang, Shuxiang (Frontiers in Pharmacology, 2025)
ObjectivesTo evaluate the therapeutic efficacy of different doses of tocilizumab (TCZ) in patients with severe or critical COVID–19.MethodsIn this single–center retrospective cohort study conducted from January 2023 to January 2024, 56 hospitalized patients with severe or critical COVID–19 who received TCZ were included. Patients were categorized into three groups based on the number of TCZ doses administered: one dose (n = 16), two doses (n = 32), and three doses (n = 8). The primary outcomes were in–hospital mortality and 30–day mortality following the first dose. Secondary outcomes included changes in inflammatory marker levels, length of hospital stay, duration of mechanical ventilation, and incidence of complications during hospitalization.ResultsAfter adjusting for potential confounders, there were no statistically significant differences in 30–day mortality (one dose vs. two doses HR 0.39; 95% CI, 0.15–1.04; P = 0.060 and one dose vs. three doses HR 0.27; 95% CI, 0.06–1.07; P = 0.067) or in–hospital mortality (one dose vs. two doses HR 0.65; 95% CI, 0.35–1.25; P = 0.090 and one dose vs. three doses HR 0.70; 95% CI, 0.40–1.50; P = 0.300) among the three groups. However, all groups showed a favorable response in inflammatory markers. Interleukin–6 (IL–6) levels initially increased after TCZ administration but subsequently declined in a fluctuating pattern. C–reactive protein (CRP) levels decreased consistently across all groups, while procalcitonin showed a modest decline. The number of TCZ doses had no significant impact on length of hospital stay, duration of mechanical ventilation, or the incidence of complications such as respiratory failure requiring mechanical ventilation, heart failure, secondary infections, thrombotic/embolic events, transaminase elevation, neutropenia, GI perforation/Haemorrhage, or acute kidney injury.ConclusionAdministering additional doses of TCZ beyond the initial dose was not associated with further reductions in mortality or improvements in other major clinical outcomes in patients with severe or critical COVID–19.